Manajemen Penggunaan Energi Baterai pada Mikrokontroler Berbasis Soft Latching Circuit - Sutoko (Universitas Islam Raden Rahmat, Malang, 2023)
In today’s increasingly massive use, batteries need special attention to how they are operated and maintained. One of the challenges faced when using batteries, especially the Li-Ion type, is monitoring, charging management and power output. The battery’s performance and quality will decrease if overcharging, over discharging, or short circuit occurs. Therefore, the role of the BMS (battery management system) is needed to regulate the charging and usage cycles of the battery. In this research, a battery energy usage management strategy is carried out which is a combination of the BMS, charger, and the ability of the microcontroller to control it on a soft latching circuit basis. In this way, the ability of the microcontroller will be targeted to help manage the efficient use of battery energy and help increase the lifespan of the battery.